METHOD OF THE COMPRESSION OF THE TRANSFORMED IMAGES IN INFO-COMMUNICATIONS BASED ON CODING OF VECTORS OF CORTEGES - Бараннік, В. В.; Туренко, С. В. (Science-based technologies, 2013)
Shown that providing video information services with using wireless communication technologies has a number of critical sides associated with the problematic regarding security of given characteristics on delay at the access point, the delay from source to destination; packet loss probability at an access point. The necessity of developing compression technologies of transformed images in a direction which based on the formation of a two-component cortege of linearized transformants in the component view is justified. Assesses of the informativeness of the truncated two-component vector of corteges in the case of structural constraints on the dynamic range is carried out. Justification of interpretation of the truncated vector of two-component corteges in the form of the integrated position number of the uncertain length which elements are codes of two-element biadic numbers formed for two-component separated corteges is stated. Development of the code forming ratio which provides code formation for integrated position number with an uncertain length on two-level schemes is stated, namely at the first level code representation for two-component separated corteges is formed, and at the second level formation of the general code for the codes received at the first level is carried out.